Transitioning from a coronary to a critical cardiovascular care unit: trends over the past three decades. Issue 4 (16th July 2020) - Ferrer, Marc; García-García, Cosme; El Ouaddi, Nabil; Rueda, Ferran; Serra, Jordi; Oliveras, Teresa; Labata, Carlos; Dégano, Irene R; Montero, Santiago; De Diego, Oriol; Elosúa, Roberto; Lupón, Josep; et al.
Abstract: Background: Coronary care units were established in the 1960s to reduce acute-phase mortality in acute coronary syndrome. In the 21st century, the original coronary care unit concept has evolved into an intensive cardiovascular care unit. The aim of this study was to analyse trend changes in characteristics and mortality of patients admitted to a coronary care unit over the past three decades. Method: Between February 1989 and December 2017, a total of 18, 334 patients was consecutively admitted to the coronary care unit of a university hospital in Barcelona. Data were analysed in five time frames: 1989–1994, 1995–1999, 2000–2004, 2005–2009 and 2010–2017. We analysed demographic profile, diagnoses at admission and trend changes in mortality across periods. Results: During the periods, the patients' ages and comorbidities increased. Diagnoses at admission have evolved. Acute coronary syndrome cases declined from the first to the last period (72.6% vs. 62.8%) while heart failure (6.0% vs. 8.6%) and malignant arrhythmias (0.8% vs. 4.0%) increased significantly. Overall, coronary care unit mortality decreased 34% from the first to the last period (6.8% vs. 4.5%, P <0.001). Furthermore, the cause of death has changed, those due to acute coronary syndrome declining (66.7% vs. 45.5%), and death from malignant arrhythmias increasing (1.9% vs. 16.2%) from the first to the last period. Conclusions: Although acute coronary syndrome remained the main diagnosis, heart failure and arrhythmias have increased. Despite the aging and comorbidities, overall mortality in the coronary care unit decreased by 34% in the past three decades. Deaths due to acute coronary syndrome have declined, whereas those due to malignant arrhythmias have increased.